Evaluasi Tata Letak Fasilitas Toko Retail Indomaret dengan Menggunakan Metode Activity Relationship Chart (ARC) - Alfi Baihaqi; Dewi Puspita Rahmawati; Lailah Azizah Syukur; Olga Tita Livia; Sari Dwina Hutapea; Shilfi Aini Yusmar (Sains: Jurnal Manajemen dan Bisnis, 2023)
Room layout is one of the important things in setting a strategy to increase productivity to realize the efficiency of a business. Spatial planning has a strategic impact on the competitiveness of the company in terms of capacity, processes, flexibility, cost, and quality of working life within the company. Indomaret is one of the retail companies that has become a well-known retail store and is very familiar to the people of Indonesia.In Indomaret outlets or retail stores spread across Indonesia, most of the layout applications are almost the same as one another, but with the differences in size and shape in each outlet, it becomes a benchmark again in the preparation of a more effective layout for Indomaret business actors. The method that can be applied in replanning this layout is the Activity Relationship Chart (ARC) Method which aims to optimize functionality between departments to prevent delays in the field of service and customer shopping processes.